Localización espacial de los puntos de venta de comidas rápidas y su impacto en la comercialización en la ciudad de Chone - Alcívar Mendoza, Gema Valentina (2023)
In a world characterized by increased exposure to competition, the location of productive activities becomes an important factor for the success of organizations. The general objective of the research was to determine the impact of the spatial location of fast-food outlets for marketing in the informal market in Chone city. The methodology used was descriptive, with a quantitative correlational approach, with a non-experimental design. The population was made up of 388 businesses from the informal market in Chone and a sample of 172 owners of the premises was drawn to apply the surveys. The data obtained were analyzed using IBM SPSS Statistics software. The instruments used for data collection were subjected to validity and reliability criteria, achieving a high level of reliability as a result. Cronbach's alpha is around 0.952; the correlation between the variables spatial location and commercialization is 0.744 Spearman's Rho and a significance level of 0.000, which demonstrates a high positive correlation. Like the correlation of each dimension that presented positive results. Given this, it is concluded that spatial location is essential to achieve the commercialization of a product. Therefore, the dimensions and location criteria must be considered to improve the marketing of the products.